The effectiveness of scientific approach-based worksheets on angiosperm classification to improve students' scientific literacy skills - Siti Nur Jihan Alfinita; Epa Paujiah; Maratus Solikha; Silmi Rahma Amelia (University of Muhammadiyah Malang, 2026)
Background: The scientific literacy skills of students in Indonesia are still relatively low due to teacher-centered learning and a lack of student scientific activity. In Angiosperm classification, learning is dominated by memorization, therefore requiring active teaching materials. Objectives: This study aims to determine the effect of using scientific approach-based worksheets on students' scientific literacy skills. Method: The study used a quantitative approach with a quasi-experimental method and a Non-Equivalent Control Group Design. The sample was obtained through cluster random sampling, involving 69 students, divided into experimental class (n = 34) and a control class (n = 35). Instruments used were a scientific literacy test, observation sheets, and student response questionnaires. Data were analyzed using the N-Gain test, the Mann-Whitney test, and the effect size. Result: The results showed that the N-Gain value for the experimental class was 0.63 (medium), while the control class was 0.07 (low). The Mann-Whitney test obtained a significance value of 0.001 (<0.05) with an effect size of 0.40 (medium), indicating a significant effect of using scientific approach-based worksheets on students' scientific literacy skills. Conclusion: Therefore, scientific approach-based worksheets can serve as an alternative teaching material to improve students' scientific literacy through active and contextual learning.